Identifikasi Saponin Pada Ekstrak Metanol Daun Pepaya (Carica Papaya Linn) Dengan Metode Kromatografi Lapis Tipis - Wa Ode Syafriah (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Traditional medicine in Indonesia has a very large role in public health services in Indonesia, so that traditional medicine has the potential to be developed. Indonesia is rich in medicinal plants, which are still not used optimally for health. This study aims to identify saponin compounds in the methanol extract of papaya leaves (Carica papaya Linn) using the Thin Layer Chromatography method. Papaya leaves (Carica papaya Linn) were extracted by maceration using methanol. Analysis of saponin compounds was carried out using the Thin Layer Chromatography method. From the results of the study, it was found that there were saponin compounds in papaya leaves (Carica papaya Linn) with an Rf value of 0.63.